Off-label versus on-label prescribing of oral oncology agents on time to receipt of medication in patients with soft tissue sarcoma. (September 2019) - Tran, Victor; Latour, Emile; Palumbo, Alison
Purpose: Off-label prescribing of oral oncology agents has been explored in the treatment of soft tissue sarcoma. The time for a prior authorization approval or rejection for an off-label use can be lengthy. The purpose of this study is to capture this burden by comparing the time it takes for patients to receive off-label versus on-label treatment for their soft tissue sarcoma. Patients and methods: In this retrospective chart review study, patients aged 18 and older who received a new prescription for an oral oncology agent for soft tissue sarcoma from one of three sarcoma providers at Oregon Health & Science University oncology clinics between March 2014 and February 2016 were included. Objectives included comparing the effect of off-label to on-label prescribing of oral oncology agents on time to receipt of medication and patient copays for a 30-day supply of oral chemotherapy agent(s). Results: The time to receipt of medication (median (IQR)) for the off-label group (N = 26) was 12.5 (3.3 to 30.8) days compared to the on-label group (N = 29), which was 8.0 (4.0 to 15.0) days (p = 0.327). The patient cost was $0.00 ($0.00 to $20.00) for the off-label group (N = 18) compared to $3.00 ($0.00 to $68.80) for the on-label group (N = 18) (p = 0.467). Conclusions: There were no differences in the time to receipt of medication or patient cost between off-label and on-label prescriptions in soft tissue sarcoma patients. Despite lack of statistical significance, these results are meaningful to patient care and require further study to investigate these findings.